A New Numerical Procedure for the Excavation Response in Mohr–Coulomb Rock Mass Exhibiting Strain-Softening Behavior - Guan, Kai; Zhang, Quanyun; Liu, Honglei; Zhu, Wancheng (Frontiers in Earth Science, 2022)
A new numerical procedure for calculating the excavation response of the Mohr–Coulomb rock mass considering strain-softening behavior is proposed in this article. In this method, the plastic zone of the strain-softening rock mass is divided into the sufficient small plastic concentric annulus with constant radial stress increment, where the stress and strain distributions are characterized based on the existing analytical solutions of the brittle–plastic rock in the plastic zone. According to the equilibrium equation, geometric equation, and Mohr–Coulomb yield criterion, the stresses of each annulus can be calculated, and the explicit form of the displacement can also be determined by invoking the non-associated flow law and Hooke’s law. On this basis, the excavation disturbance-induced response and the ground reaction curve (GRC) in the strain-softening rock mass can be calculated by iterative computation. The proposed method is verified by comparing both the numerical simulation results and the existing theoretical solutions. Extensive computations are then carried out to clarify some practical questions, including the effect of ground condition, the computation efficiency, and the engineering applicability. It is found that the proposed numerical procedure behaves more efficiently and accurately than the previous one for the strain-softening rock mass. This might, therefore, provide convenience and benefits from a computation standpoint for the preliminary design of underground openings in rock masses with slight deformation.